Mandatory audit firm rotation : the perception of Malaysian public listed companies / Suriana Mamat - Mamat, Suriana (2006)
Auditor independence is very crucial to public confidence in financial reporting. However, recent corporate failure such as in the case of Enron has critically damaged the credibility of financial reporting. Lack of auditor independence due to long-term relationships between auditor and clients is believed to be the reason for such failures. Therefore, mandatory audit firm rotation has always been proposed as a solution to enhance auditor's independence. This study aims to provide some viewpoints on whether mandatory audit firm rotation should be implemented in Malaysia considering that some countries have good experiences with it such as Italy. This study examines the value provided by mandatory audit firm rotation from the perspectives of the Chief Finance Officer of public listed companies in Malaysia. This study is based on a survey using questionnaires in order to gather the information. A total of 30 out of 100 companies re'sponded to the survey. The results indicate that mandating audit firm rotation will enhance auditor independence as perceived by the respondents. However, the respondents believe that the costs outweigh its intended benefits.